ADAPTING PEDAGOGICAL SCAFFOLDING FOR DIGITAL NATIVES THROUGH TECHNOLOGY - Hussein, Kamariah; Ali, Fariha Diyana Awang; Ne’matullah, Khairul Firdaus; Ahmad Khairundin, Siti Amalina; Shamsudin, Norazlina Hanim; Shanmugam, Jayemogen (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This conceptual article reviews the evolution of instructional scaffolding alongside the rise of digital technologies in education. Drawing on Vygotsky’s sociocultural framework and early contributions from Wood, Bruner, and Ross, traditional scaffolding centred on direct teacher-learner interaction. The shift towards online, blended, and hybrid education models now requires rethinking scaffolding approaches to meet the learning styles of digital natives. Digital scaffolding employs technological tools to deliver structured, adaptive support, while maintaining principles of contingency, gradual withdrawal, and fostering learner autonomy. This paper applies models such as Technological Pedagogical Content Knowledge (TPACK), the Community of Inquiry (CoI), and self-regulated learning (SRL) to explore effective ways of designing digital scaffolding. It also discusses barriers such as digital inequality, cognitive overload, and learner over-reliance. Finally, the paper outlines future pathways involving artificial intelligence, augmented and virtual reality, gamification, and mobile learning, offering practical insights for creating inclusive and effective pedagogical support in digital environments.